ISOLASI DAN UJI AKTIVITAS ENZIMATIK KANDIDAT PROBIOTIK DARI SALURAN PENCERNAAN IKAN-IKAN EKONOMIS RAWA DANAU PANGGANG - Rini Marlida; Elrifadah Elrifadah (Fish Scientiae, 2017)
Aim of this research were isolation of probiotics candidate from digestive tract of Danau Panggang swamp fishes and amylolitic, proteolytic, and lipolytic enzyme activity test. Sample fishes were snake head (Channa striata), climbing perch (Anabastestudineus), and Siamese gouramy (Trichogaster pectoralis) as a refresentatif sample from carnivorous, omnivorous, and herbivorous fish. Medium containing starch, skim milk and olive oil used as selective media. Result of this research was successfully isolated probiotic candidate whom grow well and had enzyme activity from C. Striata obtained 11 isolate, 12 isolate from A. testudineus and T. pectoralis respectively. Higheramilolytic activity was C3GHDP, I3PDP4 had a higher lipolytic activity, D4SSDP1 andH3PDP had a higher proteolytic activity. Among those isolate G1PDPsp had a amilolytic, proteolytic and lipolytic activity.